2021
DOI: 10.1021/acs.inorgchem.1c02804
|View full text |Cite
|
Sign up to set email alerts
|

SnS2 with Flower-like Structure for Efficient CO2 Photoreduction under Visible-Light Irradiation

Abstract: Photocatalytic CO 2 reduction using solar energy is a promising way to obtain renewable-energy sources for replacing fossil fuels. Through a hydrothermal process, we successfully designed and synthesized three-dimensional (3D) flower-like structured SnS 2 with a sheet-like structured quasi-hexagon as the building block. The 3D hierarchical structure is conducive to light capture and absorption, the sheet structure can shorten the transmission path and promote separation of the carriers, and the self-supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This definitely proves that compared with Zn–S chemical bonds, the Cu–S chemical bonds can activate CO 2 more effectively and convert it into CO quickly. According to the results of DRIFTS, it can be inferred that the pathway of CO 2 reduction to CO could be described as CO 2 → *CO 2 – → *COOH → *CO → CO. , The equation is described as follows To further investigate the reaction energy of each step in the CO 2 photoreduction process, the Gibbs free energy calculations were carried out on the pathway mentioned above, as shown in Figure e (part of the data is presented in Tables S3–S5). A relatively positive Δ G appears at the step of CO 2 adsorption on the catalyst surface, which is expressed explicitly as the slight thermodynamic hindrance of 0.32 eV for ZnIn 2 S 4 and 0.31 eV for Cu 0.7 -ZnIn 2 S 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This definitely proves that compared with Zn–S chemical bonds, the Cu–S chemical bonds can activate CO 2 more effectively and convert it into CO quickly. According to the results of DRIFTS, it can be inferred that the pathway of CO 2 reduction to CO could be described as CO 2 → *CO 2 – → *COOH → *CO → CO. , The equation is described as follows To further investigate the reaction energy of each step in the CO 2 photoreduction process, the Gibbs free energy calculations were carried out on the pathway mentioned above, as shown in Figure e (part of the data is presented in Tables S3–S5). A relatively positive Δ G appears at the step of CO 2 adsorption on the catalyst surface, which is expressed explicitly as the slight thermodynamic hindrance of 0.32 eV for ZnIn 2 S 4 and 0.31 eV for Cu 0.7 -ZnIn 2 S 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the higher specific surface area enhanced light absorption leading to a more efficient generation of electron and holes for reducing C( vi ) into Cr( iii ). Another report from You et al 135 has investigated the advantages of a flower-like morphology over nanoparticles. They observed that the flower-like structures prepared by the hydrothermal reaction have an average size of 2.39 ± 0.26 μm and a thickness of around 20 nm, which is favorable for carrier transport to the catalyst surface (Fig.…”
Section: Photocatalytic Improvement Strategiesmentioning
confidence: 99%
“…Furthermore, in the process of photocatalytic CO 2 reduction, the first step is the capture and absorption of light by the catalyst, so the morphology of the catalyst plays an important role. [27,28] The hollow structure with confined space is a very good choice. As for hollow structure applied in photocatalysis, the incident light can be multiscattered/reflected in the cavity, increasing the optical path to improve the capture and utilization of light.…”
Section: Introductionmentioning
confidence: 99%